Institutional Traps in the Scientific and Educational Sphere: Nature and Mechanism of Elimination - Е. V. Romanov (Russian State Vocational Pedagogical University, 2020)
Introduction. One of the consequences of the crisis associated with the coronavirus pandemic will be increased global competition for human capital. Russia's ability to create barriers to "brain drain" will determine how quickly to overcome the crisis and enter the sixth technological order. Improving the efficiency of the educational system (primarily higher education) as a "basis" for training scientists, who can provide "breakthrough" scientific results, actualises the research aimed at eliminating ineffective standards, which set false benchmarks for the innovative development of higher education and science. The aim of the present research is to identify the nature of institutional traps in the scientific and educational sphere and to suggest the ways to eliminate them. Methodology and research methods. The current research was carried out on the basis of a systematic approach. The following general scientific methods were employed: analytical review of scientific literature and the content of normative documents, generalisation, comparison, synthesis. Results and scientific novelty. The author's hypothesis that the backbone of the institutional trap in the scientific and educational sphere is the trap of strategic planning in the formal documents, which should set strategic guidelines of development of higher education and science, the real content of these documents does not represent: a) the structure of trained personnel (the proportion of graduates, who studied under secondary professional and higher education programmes); b) the planned number of future specialists in specialties and areas of training, which are critical for a breakthrough in the sixth technological order; с) the necessary and sufficient number of researchers, who can provide "breakthrough" scientific results; d) the necessary and sufficient number of higher school teachers, who can provide high-quality transfer of "compressed" human experience. In the scientific sphere, the phenomenon of "implicit knowledge deficit" is recorded: against the background of an increase in the proportion of young researchers (up to 39 years of age), the number and proportion in the cohort of middle-aged researchers (40-59 years) decreases. In higher education, there is a "surplus of implicit knowledge": a decrease in the share of young teachers with a fairly stable share of middle-aged teachers creates a situation, where there is no one to transmit implicit knowledge to. Cumulatively, this can prevent real scientific results from being obtained and promoted in the real economy and commercialisation, as well as lead to imitation of scientific research and the absence of "breakthrough" scientific results. The analysis of approaches used by the Ministry of Education and Science of the Russian Federation to assess the effectiveness of universities and research organisations suggests the existence of a "performance evaluation trap", when the proposed methods do not allow making an objective conclusion about the essence of the measured. The trap of strategic planning in the scientific and educational sphere predefined the paradoxes of strategic planning in the Russian Federation when the development of strategies and programmes for the promotion of crucial sectors of the national economy is not based on forecasting long-term socio-economic development of Russia. Based on the generalisation of the results of the analysis, the proposals are formulated, which should be kept in a reference framework for a national-oriented strategy for the development of the scientific and educational sphere. Practical significance. The research results can be used to adjust the strategy for the development of scientific and educational sphere.